Investigation of the oxidative folding pathway in Trypanosoma brucei - Millerick, Michael I. (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2013)
In eukaryotic organisms the native structure of proteins destined to be secreted, such as immunoglobulins, or mounted surface proteins rely on the formation of disulphide bridges between cysteine residues for structural integrity. These bonds are thought to be formed in the endoplasmic reticulum via a pathway commonly referred to as the oxidative folding pathway.
Keywords: Biochemistry & Immunology, Ph.D.; Ph.D. Trinity College Dublin.